The influence of teacher pedagogical competence of teachers’ work morale - Nellitawati Nellitawati (RedWhite Press, 2020)
This study aims to analyze the influence of teacher pedagogical competence on teacher’s work morale. Using a quantitative approach through the correlational method. The research sample of 86 teachers. Data collection uses two instruments, the teacher’s pedagogical competency questionnaire, and the teacher’s work moral questionnaire. Data analysis techniques used One-Sample Kolmogorov-Smirnov for normality tests and simple regression techniques for linearity tests. The results showed that increasing teacher pedagogical competence influenced increasing teacher morale. It can be concluded that the teacher's pedagogical competence needs to be improved so that the teacher's work morale also increases so that educational goals can be realized.